Changes of Internal State Are Expressed in Coherent Shifts of Neuromuscular Activity in Aplysia Feeding Behavior - Zhurov, Yuriy (J Neurosci, 2005)
The multitasking central pattern generator (CPG) that drives consummatory feeding behaviors of Aplysia can produce ingestive, egestive, and intermediate motor programs. External stimuli trigger the programs but, remarkably, do not directly specify which type of program is produced. Rather, recent work has proposed, the type of program is determined by the internal network state of the CPG that has developed in response to the previous history of the stimulation. Here we have tested a key prediction of this network-state hypothesis. If the network state has a real existence and governs real functional behavior, changes in the state should be seen as coherent, coordinated changes along many dimensions of interneuron and motor neuron activity, muscle contraction, and ultimately movement, that underlie functional behavior. In reduced neuromuscular preparations, we elicited repetitive motor programs by continued stimulation of the esophageal nerve while recording the firing of motor neurons B8, B15, B16, B4/5, and B48, and contractions of the accessory radula closer and I7-I10 muscles that respectively close and open the animal's food-grasping organ, the radula. Using sonomicrometric techniques, we similarly recorded the movement of the radula in the complete buccal mass. Successive esophageal nerve programs indeed exhibited clear progressive changes in motor neuron firing, muscle contractions, and the phasing of radula movements within each cycle, from an initially intermediate or even ingestive character to a strongly egestive character. We conclude that the Aplysia feeding CPG really has a coherent internal network state whose dynamics are likely to be reflected in the real behavior of the animal.